FINANCIAL BEHAVIOR AND FINANCIAL WELL-BEING AMONG WORKING STUDENTS - Yandi Suprapto; Fiona Siah; Candy Candy (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study examines the relationships between financial literacy, self-control, financial behavior, financial stress and financial well-being among working university students in Batam City. Prior research has shown inconsistent findings regarding how these variables relate to financial well-being. Specifically, this study investigates both direct and indirect effects through financial behavior as a mediator. This research also aims to identify which factors contribute most significantly to improving the financial well-being of working university students.METHODOLOGY - A quantitative approach with explanatory research was used in this study. Data were collected from 418 working university students in Batam City via an online questionnaire using purposive sampling with a 1-5 Likert scale. Data analysis was conducted using PLS-SEM.FINDING - The results reveal that financial literacy together with self-control shapes financial behavior. However, financial literacy and self-control exert no influence on financial well-being. Financial stress significantly and negatively harms financial well-being, while financial behavior shows no significance in influencing financial well-being. Furthermore, financial behavior fails to mediate the relationship between financial literacy and self-control on financial well-being. These findings suggest that reducing financial stress is more relevant. Therefore, institutions should prioritize reducing financial stress through providing direct support such as scholarships, affordable micro-loans and part-time job programs, rather than focusing solely on financial literacy education.